2007
DOI: 10.1007/s10620-007-9985-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the PHQ-9 as a Screening Tool for Depression in Patients with Chronic Hepatitis C

Abstract: Approximately 52% of participants reported symptoms suggesting depression. Prevalence of depression was 62% using the BDI-II, 75% per the PHQ-9 and 72% per the CES-D. We observed a strong correlation between the BDI-II, CES-D and PHQ-9 in patients on and off interferon. Scores on the three questionnaires were only moderately associated with symptoms reported by the patients. There was moderate agreement between the CES-D and BDI-II and slight agreement between both these questionnaires and the PHQ-9. Scores on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
21
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 32 publications
(38 reference statements)
6
21
0
Order By: Relevance
“…An earlier study assessed the PHQ-9 as a screening tool for depression in patients with chronic hepatitis C, comparing performance against 2 other screening questionnaires-the Center for Epidemiologic Studies Depression Scale and the BDI. 17 It found a strong correlation between the BDI and the PHQ-9, consistent with our results. Patients currently on interferon were included in the sample, which may have LR À indicates the negative likelihood ratio is the false negative rate divided by the true negative rate; LR+, the positive likelihood ratio is the true positive rate divided by the false positive rate and can be used to find the posttest odds, using formula: posttest odds=pretest odds ÂLR+; MINI, Mini International Neuropsychiatric Interview; PHQ-9, Patient Health Questionnaire-9.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…An earlier study assessed the PHQ-9 as a screening tool for depression in patients with chronic hepatitis C, comparing performance against 2 other screening questionnaires-the Center for Epidemiologic Studies Depression Scale and the BDI. 17 It found a strong correlation between the BDI and the PHQ-9, consistent with our results. Patients currently on interferon were included in the sample, which may have LR À indicates the negative likelihood ratio is the false negative rate divided by the true negative rate; LR+, the positive likelihood ratio is the true positive rate divided by the false positive rate and can be used to find the posttest odds, using formula: posttest odds=pretest odds ÂLR+; MINI, Mini International Neuropsychiatric Interview; PHQ-9, Patient Health Questionnaire-9.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, researchers were not able to validate the PHQ-9 as a gold standard was not used. 17 Another study found moderate agreement between the BDI and the MINI in patients with chronic kidney disease, 18 also consistent with our results. The discrepancies between the BDI and the MINI may be because of selfreport of depressive symptoms versus clinical depression.…”
Section: Discussionsupporting
confidence: 89%
“…The PHQ-9 has been shown to be a reliable and valid measure of depression severity in primary care 7 and physically ill populations in secondary care. [10][11][12] The GAD-7 is a reliable and valid measure of anxiety in primary care, 8 the general population 13 and secondary care. 14 The DLQI is widely used in dermatology for research purposes and has adequate validity and reliability.…”
Section: Procedurementioning
confidence: 99%
“…a group in another English-speaking country, one with a specific illness or one based in primary care). 85,[94][95][96][97] No such field testing had yet been carried out with the BSL population. Furthermore, the analysis of a large data set of patients who had used BSL-IAPT in terms of referral rates, adherence and clinical outcomes would enable calculation of recruitment targets should a full trial be indicated.…”
Section: Introductionmentioning
confidence: 99%